Comparison of KRAS mutation analysis of colorectal cancer samples by standard testing and next-generation sequencing. Issue 9 (8th July 2014) - Kothari, Nishi; Schell, Michael J; Teer, Jamie K; Yeatman, Timothy; Shibata, David; Kim, Richard
Abstract : Aims: Based on KRAS testing, the subset of patients with metastatic colorectal cancer (CRC) that could benefit from anti-EGFR therapy can be better delineated. Though KRAS testing has become significantly more prevalent over the last few years, methods for testing remain heterogeneous and discordance has been reported between methods. Methods: In this study, we examined a CRC patient population and compared KRAS testing done in Clinical Laboratory Improvement Amendments (CLIA) approved laboratories as part of standard clinical care and by next-generation sequencing (NGS) using the Illumina platform. Discordances were further evaluated with manual review of the NGS testing. Results: Out of 468 CRC patient samples, 77 had KRAS testing done by both CLIA assay and NGS. There were concordant results between testing methodologies in 74 out of 77 patients, or 96% (95% CI 89% to 99%). There were three patient samples that showed discordant results between the two methods of testing. Upon further investigation of the NGS results for the three discordant cases, one sample showed a low level of the mutation seen in the standard testing, one sample showed low tumour fraction and a third did not show any evidence of the mutation that was found with the standard assay. Five patients had KRAS mutations not typically tested with standard testing. Conclusions: Overall there was a high concordance rate between NGS and standard testing for KRAS. However, NGS revealed mutations that are not tested for with standard KRAS assays that might have clinical impact with regards to the role for anti-EGFR therapy.